Long-term effect of efavirenz autoinduction on plasma/peripheral blood mononuclear cell drug exposure and CD4 count is influenced by UGT2B7 and CYP2B6 genotypes among HIV patients - Habtewold, Abiy; Amogne, Wondwossen; Makonnen, Eyasu; Yimer, Getnet; Riedel, Klaus-Dieter; Ueda, Nobuhisa; Worku, Alemayehu; Haefeli, Walter E.; Lindquist, Lars; Aderaye, Getachew; Burhenne, Jürgen; Aklillu, Eleni (The journal of antimicrobial chemotherapy, 2011)
AbstractObjectives. We investigated the long-term effect of efavirenz autoinduction on its plasma/peripheral blood mononuclear cell (PBMC) exposure and the CD4 count, and the importance of sex and pharmacogenetic variations.